Gynaecologists’ awareness of bone healthcare in Switzerland (Swiss Medical Weekly, 2014)
PRINCIPLES: To assess gynaecologists’ awareness of bone healthcare in women and the prevalence of application of national recommendations on bone healthcare in Switzerland. METHODS: During the annual meeting of the Swiss Society of Gynaecology and Obstetrics 2012, the Swiss Association against Osteoporosis (SVGO) performed standardised interviews with conference participants (n = 210). Questions addressed responsibility for bone healthcare, and whether diagnostic procedures, initiation of bone-specific treatment and follow-up were performed in accordance with SVGO recommendations. RESULTS: The majority of respondents were aged 30–50 years (60%), female (70%) and working as board-certified gynaecologists (69%). Ninety-three percent of respondents considered care for bone health as part of the gynaecologist’s expertise. As diagnostic procedures, 44% recommended performing bone densitometry (DXA) only, 34% ordered additional laboratory testing. Seventy-two percent of respondents initiated a bone-specific treatment. Predictors for not performing diagnostic procedures and not initiating a bone-specific treatment were physician’s age below 30, being a trainee gynaecologist, and working at a university clinic. Particularly, young trainee gynaecologists working at a university clinic were especially unlikely to initiate a bone-specific treatment (regression coefficient = –2.68; odds ratio [OR] 0.069, 95% confidence interval [CI] 0.01–0.61; p = 0.16). Follow-ups were performed by 77% of respondents, but were less likely to be by female physicians (OR 0.27, 95% CI 0.09–0.84; p = 0.024). CONCLUSIONS: Although the majority of board-certified gynaecologists follow national recommendations on bone healthcare, current medical training in obstetrics and gynaecology does not sufficiently cover the subject of women’s health. However, since this is a small study our findings may not reflect the findings in the total population.